Characterization of two different alginate-based bioinks and the influence of melanoma growth within - Schipka, Raphael; Heltmann-Meyer, Stefanie; Schneidereit, Dominik; Friedrich, Oliver; Röder, Jonas; Boccaccini, Aldo R.; Schrüfer, Stefan; Schubert, Dirk W.; Horch, Raymund E.; Boßerhoff, Anja Katrin; Arkudas, Andreas; Kengelbach-Weigand, Annika; et al. (Scientific Reports, 2024)
Extrusion-based bioprinting is an established method in biofabrication. Suitable bioinks have fundamentally different compositions and characteristics, which should be examined, in order to find a perfect model system. Here, we investigate the effect of two alginate-based, yet unalike 3D-printed bioinks, pre-crosslinked alginate-dialdehyde gelatin (ADA-GEL) and a mixture of alginate, hyaluronic acid, and gelatin (Alg/HA/Gel), on the melanoma cell line Mel Im and vice versa in terms of stiffness, shrinkage, cellular behavior and colony formation over 15 days. Rheological stiffness measurements revealed two soft gels with similar storage moduli. The cells did not have a significant impact on the overall stiffness, whereas ADA-GEL (2.5/2.5%) was significantly stiffer than Alg/HA/Gel (0.5/0.1/3%). Regarding the shrinkage of printed constructs, cells had a significant influence, especially in ADA-GEL, which has covalent bonds between the oxidized alginate and gelatin. Multi-photon microscopy exhibited proliferation, cell spreading and migration in ADA-GEL with cell–cell and cell–matrix interaction, dissimilarly to Alg/HA/Gel, in which cells formed spherical, encapsulated colonies. Scanning electron microscopy and histology showed degradation and multi-layered growth on ADA-GEL and fewer examples of escaped cells on Alg/HA/Gel. Both gels serve as proliferation bioink for melanoma with more necrosis in deeper Alg/HA/Gel colonies and differences in spreading and matrix interaction. These findings show the importance of proper characterization of the bioinks for different applications.
CRIS-Team Scopus Importer:2024-06-14
Keywords: 3D-printing; Alginate; Hydrogel; Melanoma; Stiffness